Asymptomatic extraperitoneal inguinoscrotal hernia involving ureter: A case presentation and review of the literature - Falidas, Evangelos (J Nat Sci Biol Med, 2015)
An inguinoscrotal hernia is a common disorder that usually contains intraperitoneal organs (small intestine, colon, appendix, ovaries). Extraperitoneal ureteral herniation into an inguinoscrotal hernia is a rare condition and often associated with congenital abnormalities or postoperative anatomic changes. A high index of suspicion is needed in order to avoid intraoperative ureteric injuries. We herein report the case of a ureteric herniation into an inguinoscrotal hernia incidentally found during a scheduled hernia repair.